The Application of Peer Tutor Method in Fiqh Learning to Form Student Characters at MTs Integrated Pesantren Al Fauzan Lumajang - Alwi, Muhamad Muksin (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2025)
In order to enhance the character development of students, particularly at the junior secondary level, the use of competitive and interactive learning methods is essential. Thematic learning through the Peer Tutoring method has been implemented at Madrasah Tsanawiyah Pesantren Terpadu Al Fauzan Lumajang as an engaging instructional approach. This method enables students to collaborate, engage in discussions, develop mutual respect, offer assistance to peers, and express their opinions with greater confidence. Peer tutoring fosters a supportive learning environment that contributes to students’ personal and social character growth. This study focuses on three main objectives: identifying the character traits developed through Fiqh learning using the Peer Tutoring method, describing the instructional process of Fiqh through peer-assisted learning, and evaluating the effectiveness of this method in shaping students’ character at Madrasah Tsanawiyah Pesantren Terpadu Al Fauzan. The purpose of this research is to describe and analyze the character values cultivated in Fiqh learning through peer tutoring, examine the implementation process of the method in fostering students’ character, and evaluate the impact of the method on students’ behavioral and moral development.